Case Report: Successful Management and Long-Term Follow-Up of Bilateral Ureteral Ligation in a Dog Secondary to Cryptorchid Castration Utilizing Bilateral Ureteral Stents and a Neoureterocystostomy Procedure - Walton, Rebecca; Mickelson, Megan; Palerme, Jean-Sebastien; Blong, April; 't Hoen, Meredith (Frontiers in Veterinary Science, 2022)
Objective: To report the successful management of bilateral ureteral obstruction secondary to ureteral ligation during unilateral cryptorchid surgery in a dog with the utilization of bilateral ureteral stent placement and a neoureterocystostomy procedure. Summary: A 7-month-old male castrated Weimaraner weighing 30 kg presented to a university teaching hospital for evaluation of a 4-day history of lethargy, vomiting, and stranguria following exploratory laparotomy for a left-sided unilateral cryptorchid castration. Based on the concurrent presence of severe azotemia and ultrasonographic findings of bilateral hydronephrosis and hydroureter, the dog was diagnosed with suspected bilateral ureteral obstruction. The dog underwent a laparotomy which revealed bilateral ureteral ligation which was corrected with a left-sided neoureterocystostomy and right-sided retrograde ureteral stent placement. Subsequent placement of a left-sided ureteral stent due to complications with the neoureterocystostomy site was later performed. Ultimately both ureteral stents were able to be removed a few months later. The dog was clinically doing well with a baseline creatinine of 1.5 mg/dL (132.6 umol/L) 532 days following initial bilateral ureteral ligation. New or Unique Information Provided: This case report describes the successful long-term management of iatrogenic bilateral ureteral obstructions in a male dog using a combination of bilateral ureteral stents and neoureterocystostomy.